Penentuan Metode Intervensi untuk Mengurangi Beban Kerja Mental pada Karyawan Laboratorium Produksi 1A PT. XYZ Menggunakan Analytical Hierarchy Process - Ramadani Nur Cholis; Idha Rahayuningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Mental workload has a significant influence on employee performance in doing work. PT XYZ is a state-owned company engaged in the agro-industrial sector that produces fertilizer and non-fertilizer products. To maintain the quality of raw materials to products, laboratory personnel are needed. Production laboratory personnel 1A PT. XYZ has a routine job of analyzing raw materials and by-products to main products. This study aims to identify the mental workload of 1A production laboratory employees and identify appropriate intervention methods to reduce mental workload. The process of measuring mental workload uses the NASA-TLX scale and the AHP method to determine the proper intervention method. The results of this study showed that 26% of employees experienced a high mental workload. The selected intervention using the AHP method to reduce mental workload is meditation.